2021
DOI: 10.3390/biomedicines9030304
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Adrenocortical Carcinoma: Predictors of Response, Efficacy, Safety, and Mechanisms of Resistance

Abstract: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with limited treatment options in the advanced stages. Immunotherapy offers hope for altering the orthodox management of cancer, and its role in advanced ACC has been investigated in different studies. With the aim clarifying the role of immunotherapy in ACC we performed a comprehensive review about this topic focusing on the predictors of response, efficacy, safety, and the mechanisms of resistance. Five clinical trials with four immune checkpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 112 publications
0
20
0
1
Order By: Relevance
“…Immunotherapy provides new options for altering the routine strategies of advanced ACC, and the value of immune checkpoint inhibitor (ICI) therapy has been proposed in many studies. However, the results of a multicenter study of four ICI drugs hint at a poor overall response rate and progression-free survival in treating ACC [ 48 ]. Several pathway alterations and molecular alterations may be responsible for ICI therapy resistance, and further immunological markers of response might solve this dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy provides new options for altering the routine strategies of advanced ACC, and the value of immune checkpoint inhibitor (ICI) therapy has been proposed in many studies. However, the results of a multicenter study of four ICI drugs hint at a poor overall response rate and progression-free survival in treating ACC [ 48 ]. Several pathway alterations and molecular alterations may be responsible for ICI therapy resistance, and further immunological markers of response might solve this dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical response rates still lack major breakthrough success and the tumor microenvironment, which is of importance for response and resistance patterns to this kind of therapy, appears particularly complex. One key point is the impact of corticosteroid-induced immune cell depletion, causing lower numbers of circulating lymphocytes, and a high load of T-cell suppressive CD276 (B7-H3), in addition to low levels of classical biomarkers for immunotherapy including PD-L1, tumor mutational burden (TMB), TILs and MSI-H. 83 , 90 Other factors discussed as mechanisms of resistance to immunotherapy in ACC are alterations in the WNT–beta-catenin pathway that cause changes to the CD8+ population in the tumor microenvironment and alter the specific immune response. 90 Furthermore, TP53 inactivation can decrease production of cytokines necessary for immune effector cell invasion.…”
Section: Systemic Treatment – Are We Making Progress?mentioning
confidence: 99%
“…One key point is the impact of corticosteroid-induced immune cell depletion, causing lower numbers of circulating lymphocytes, and a high load of T-cell suppressive CD276 (B7-H3), in addition to low levels of classical biomarkers for immunotherapy including PD-L1, tumor mutational burden (TMB), TILs and MSI-H. 83 , 90 Other factors discussed as mechanisms of resistance to immunotherapy in ACC are alterations in the WNT–beta-catenin pathway that cause changes to the CD8+ population in the tumor microenvironment and alter the specific immune response. 90 Furthermore, TP53 inactivation can decrease production of cytokines necessary for immune effector cell invasion. However, based on the given data, immunotherapy may be applied in selected patients if available – not least due to the sobering results of chemotherapy-based salvage regimens.…”
Section: Systemic Treatment – Are We Making Progress?mentioning
confidence: 99%
“…Therefore, it was urgently needed to analyze the relationship between ferroptosis score and immune factors in ACC. PD-1, PD-L1, and TMB were the main potential markers of response to immunotherapy in ACC [19]. Our study showed that ferroptosis scores were positively related to the expression of PD-L1 and were negatively related to the expression of TMB.…”
Section: Discussionmentioning
confidence: 48%